2020
DOI: 10.3345/cep.2020.00073
|View full text |Cite
|
Sign up to set email alerts
|

Association between assisted reproductive technology and autism spectrum disorders in Iran: a case-control study

Abstract: Background: Autism spectrum disorder (ASD) is a neurodevelopmental disorder defined by impairments in social interaction and verbal and nonverbal communication.Purpose: Determine the association between use of assisted reproduction technology (ART) and the risk of ASD among children.Methods: This case-control study included 300 participants (100 cases, 200 controls). The control group included women with a child aged 2–10 years without ASD, while the cases were women with a child aged 2–10 years with ASD. We u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…4) Evidence suggests that the risk factors for ASD are preterm birth, preeclampsia-assisted reproductive technology (ART), and neonatal jaundice. [5][6][7][8] The relationship between small for gestational age (SGA) and ASD remains conflicting. Studies examining gestational age at birth and ASD reported different findings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4) Evidence suggests that the risk factors for ASD are preterm birth, preeclampsia-assisted reproductive technology (ART), and neonatal jaundice. [5][6][7][8] The relationship between small for gestational age (SGA) and ASD remains conflicting. Studies examining gestational age at birth and ASD reported different findings.…”
Section: Introductionmentioning
confidence: 99%
“…These numerous abnormalities indicate that etiologically, the period of causation may theoretically be in utero or early infancy [ 4 ]. Evidence suggests that the risk factors for ASD are preterm birth, preeclampsia-assisted reproductive technology, and neonatal jaundice [ 5 - 8 ]. The relationship between small for gestational age (SGA) and ASD remains conflicting.…”
Section: Introductionmentioning
confidence: 99%
“…There have been broad discussions about whether the use of ART is associated with the diagnosis of autism spectrum disorders (ASD) in the offspring. While most studies were unable to find any associations ( Sandin et al, 2013 ; Lung et al, 2018 ; Jenabi et al, 2020 ; Farhi et al, 2021b ), a few studies reported a significantly higher risk for ASD in ART offspring ( Fountain et al, 2015 ; reviewed in Liu et al, 2017 ). However, the effect was substantially reduced when adverse prenatal and perinatal outcomes and demographics were taken into account ( Fountain et al, 2015 ).…”
Section: Cognitive and Neurodevelopmental Health Of Newborns And Chil...mentioning
confidence: 99%
“…One study was conducted in Finland and studied 4164 cases with autism and 16,582 matched controls born in 1991–2005 [ 30 ]. Another study was conducted in Iran, and it included 100 cases with ASD and 200 controls between 2 and 10 years of age [ 27 ].…”
Section: Resultsmentioning
confidence: 99%